ANALISIS PERMASALAHAN GURU DALAM PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Mai Sri Lena; Hana Shilfia Iraqi; Ima Putri; Elsa Nurul Fauziah (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The purpose of the research is to describe various teacher problem implementing unified thematic learning in elementary schools. This study used qualitative research methods. Respondents in this study were teachers who teach in elementary schools. Data collection techniques through questionnaires distributed to teachers who teach in elementary schools. The results obtained from this study are: teachers have several problems in carrying out integrated learning such as not having interest in and understanding how to make learning media, lack of management of time allocation during learning, limited learning facilities and infrastructure they have, not mastering technology so they are unable to make technology-based media, have not been able to integrate or combine learning materials in accordance with predetermined provisions, still use the lecture method and have not used various kinds of learning resources. Therefore, the research results can be used as material for evaluating teachers in implementing thematic learning in elementary schools.